LEXICAL AND GRAMMATICAL FEATURES OF METAPHORS - Suyarova Nargiza Yuldoshevna; Tursunali Jumayev (Modern American Journals, 2025)
This article discusses the specific lexical and grammatical features of metaphors, the peculiarities of grammatical transposition in Uzbek and English, and a number of regularities reflecting these features. It also highlights the presence of similar constructions in English and Uzbek, as well as their structural and functional characteristics.
Keywords: Metaphor, metaphorization, lexical and grammatical features, grammatical transposition, complex system, grammatical category, grammatical role.